2022
DOI: 10.1038/s41467-022-28774-y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling assortative mating and genetic similarities between partners, siblings, and in-laws

Abstract: Assortative mating on heritable traits can have implications for the genetic resemblance between siblings and in-laws in succeeding generations. We studied polygenic scores and phenotypic data from pairs of partners (n = 26,681), siblings (n = 2,170), siblings-in-law (n = 3,905), and co-siblings-in-law (n = 1,763) in the Norwegian Mother, Father and Child Cohort Study. Using structural equation models, we estimated associations between measurement error-free latent genetic and phenotypic variables. We found ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(89 citation statements)
references
References 62 publications
6
78
4
1
Order By: Relevance
“…This suggests that AM for EA is consistent with genetic homogamy, and that mates may be assorting on some trait that is more genetically than environmentally correlated with EA. Contrary to Robinson et al's (2017) 32 finding, Torvik et al (2022) 48 did not find evidence for genetic homogamy in educational attainment in a sample of partners, siblings, and in-laws in Norway. Instead, they found evidence that AM on EA was due to a mix of both social homogamy and phenotypic homogamy.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This suggests that AM for EA is consistent with genetic homogamy, and that mates may be assorting on some trait that is more genetically than environmentally correlated with EA. Contrary to Robinson et al's (2017) 32 finding, Torvik et al (2022) 48 did not find evidence for genetic homogamy in educational attainment in a sample of partners, siblings, and in-laws in Norway. Instead, they found evidence that AM on EA was due to a mix of both social homogamy and phenotypic homogamy.…”
Section: Discussionmentioning
confidence: 68%
“…Contrary to Robinson et al’s (2017) 32 finding, Torvik et al . (2022) 48 did not find evidence for genetic homogamy in educational attainment in a sample of partners, siblings, and in-laws in Norway. Instead, they found evidence that AM on EA was due to a mix of both social homogamy and phenotypic homogamy.…”
Section: Discussionmentioning
confidence: 84%
“…In fact, earlier experiments (data not shown) indicate that for certain other traits (Height and BMI) this effect is also present. This suggest the effect could be caused by assortative mating, since there is a significant body of evidence suggesting assortative mating effects for these effected traits [44, 24, 49, 37]. Also, we feel it is worth noting that this very discrepancy might be exploited as a measure of assortative mating.…”
Section: Discussionmentioning
confidence: 92%
“…26 However, a large Australian study found that spousal convergence played a negligible role in partner similarity for EA, 27 and recent molecular genetic studies have found strong evidence for phenotypic assortment on EA and/or associated traits. [28][29][30][31][32][33] A recent Norwegian study estimated the genetic correlation between spouses for EA at 0.37. 32 It also estimated the genetic correlation between siblings at 0.67 -a figure which suggests that CTD estimates of EA have been doubling the difference between MZ and DZ twin correlations to estimate heritability when tripling the difference might be more appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32][33] A recent Norwegian study estimated the genetic correlation between spouses for EA at 0.37. 32 It also estimated the genetic correlation between siblings at 0.67 -a figure which suggests that CTD estimates of EA have been doubling the difference between MZ and DZ twin correlations to estimate heritability when tripling the difference might be more appropriate. Martin (1978) 34 developed a method to correct CTD ACE estimates for bias due to assortative mating when data on spousal correlations for parents is available.…”
Section: Introductionmentioning
confidence: 99%